Atomic Diffusion and Molecular Self-Assembly on Metal Surfaces. - Jewell, April. (2017)
Abstract: The research described herein focuses on understanding and exploiting nanometer-scale surface phenomena with respect to surface reactivity and self-assembled systems. Using scanning tunneling miscroscopy, atoms and small molecules (i.e., fewer than 30 atoms) adsorbed on metal surfaces were studied with the objective being to capture, understand, and manipulate the events occurring at the interface between gases and solid surfaces. The specific approach was to examine a variety of different but related chemical species in order to understand how chemical functionality affects the assembly behavior of technologically important species on metal surfaces. Using this systematic approach, in which, for example, only a single atom (or group of atoms) in the adsorbed species was varied, it was possible to uncover subtle differences in assembly behavior and overlayer stability. These differences are explained in terms of the chemical properties of the differing atom(s), which are based on well-established periodic trends and governed by electrostatics. Similar studies focusing on varying ligand functionality are also presented. Findings from this research add to our understanding of fundamental chemical interactions that govern assembly at the gas/solid interface. Importantly, the work here contributes to the establishment of heuristic rules that, in the future, could help predict assembly behavior. The impact of this research has the potential to transform our approach to sensor technology, heterogeneous catalysis, and other related fields.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Chemistry.; Advisor: Charles Sykes.; Committee: Elena Rybak-Akimova, Albert Robbat, and Karsten Pohl.; Keywords: Chemistry, Physical chemistry, and Nanoscience.